Dynamic Modeling and Control Law Design of a Fuel-electric Hybrid Multi-rotor UAV. (February 2022) - Xu, Xice; Lu, Yang; Wu, Xufeng
In this paper, the design of control law for a new concept fuel-electric hybrid multi-rotor UAV with lift/attitude control separation is investigated. The remarkable feature of the UAV is that it has a large proportion of fuel weight. Firstly, based on the quasi-coordinate Lagrangian equation and sloshing equivalent model using the multi-mass-spring analogy, the non-linear dynamic model of the UAV considering the fuel slosh dynamics is established. Compared with the existing multi-rotor modeling method, it is more intuitive and accurate to describe the non-linear coupling process of sloshing and UAV's motion degrees of freedom. Secondly, the attitude control law is designed based on the finite-time sliding mode observer and cascaded continuous sliding mode controller to eliminate the adverse effects of fuel sloshing and mass changing, and only using the measurable angles. Furthermore, aiming at the problem of power redundancy of the altitude channel, a memoryless non-linear altitude authority assignment controller based on vertical acceleration is proposed for improving the control performance. Finally, the simulation results of the waypoint flight illustrate the feasibility and effectiveness of the proposed control strategy.